Reproductive timing and clutch parameters of the pearl darter, Percina aurora , in the Pascagoula River drainage - Malia B. Davidson; Noah J. Daun; Scott R. Clark; Brian R. Kreiser; Jake F. Schaefer (Journal of Fish Biology, 2026)
Understanding the timing, duration and effort put into reproduction is vital to successful management of any species. The southeastern United States is home to tremendous levels of aquatic biodiversity and was recently named one of the Earth's biodiversity hotspots. For some species, the fundamentals of age, growth, reproductive timing and ecology remain poorly understood. Percina aurora , the pearl darter, has been recently listed as threatened due to its contracting range, likely due to anthropogenic pressure on these systems. However, management efforts are hindered by the lack of knowledge about the life history of P. aurora . The purpose of this project was to examine the age, growth and reproductive ecology of P. aurora in the Pascagoula River basin of southeastern Mississippi, USA. To do this, we compiled length data from recent field collections and catalogued museum specimens to estimate age and growth, as well as clutch parameters (GSI, egg size) to infer reproductive output. We also used larval fish metabarcoding to confirm successful spawning of P. aurora . These results indicate P. aurora exhibits a protracted, potentially batch‐spawning reproductive strategy with consistent spawning timing across rivers, supported by both growth models and larval detections.